Rescue 991: The Malaysian Civil Defence Emergency System / Siti Azrin Abdul Aziz - Siti Azrin, Abdul Aziz (2001)
The Rescue 991 Emergency Line has emerged since a few year back and has been reserved for the use of The Civil Defence Force of Malaysia, which was first brought forth in the year 1952. The Civil Defence Force of Malaysia is a government department which handles emergency cases especially those regarding with accidents di asters and war. The Rescue 991 Emergency Line has been officially launched on the 20°1 May 1995 on the emergency line for The Civil Defence Force for Kuala Lumpur and Klang Valley. Because of the encouraging responses received in Klang Valley, the emergency line ha widened it coverage throughout Malaysia by 1998. The latest addition to The Rescue 991 Emergency Line is the proposed system of The Rescue 991 Emergency System. Since the existence of The Rescue 991 Emergency Line, emergency cases have been handled manuly. As with manually managed systems, problems and restriction arise as part of the system. Part of the problems and restrictions, which arise, are that management of emergency cases have been slow and unproductive. The development of Rescue 991 Emergency System is anticipated to include the use of information Technology in this important and essential service. The Rescue 991 Emergency System is designed in hope that it may generate an interest among users towards the modern technology with its attractive yet simple user interface. It is time for The Malaysian Civil Defence Force's rescue team to be in sync with the technologies of the millennium.